SUBTITUSI PASTA TALAS BELITUNG (XANTHOSOMA SAGITTIFOLIUM (L.) SCHOTT), TEPUNG TEMPE KEDELAI DAN TEPUNG TAPIOKA DALAM PEMBUATAN MIE BASAH UNTUK PENDERITA DIABETES MELITUS - Ika Heri Kustanti; Astutik Pudjirahaju; Suliastutik Suliastutik; Theresia Puspita (Faculty of Agricultural Technology, University of Jember, 2013)
Prevalence of Diabetes Mellitus (DM) is increasing from year to year. One alternative of therapy for diabetic is healthy diet to reduce elevated levels of blood glucose and reduce of clinical symptoms that may increase the risk of complications. One alternative is the use of local food consumption belitung taro that have a low GI and carbohydrate sources. Wet noodle is one alternative to increase the added value of taro belitung. In a wet noodle processing can be substituted soybean cake flour and tapioca flour to increase nutritional value. The purpose of research analyzing the effect of substitution belitung taro paste, soybean cake flour and tapioca flour to the value of the energy, chemical quality, physical quality and organoleptic test wet noodle for diabetic. Types of experimental studies with research designs completely randomized design (CRD). Level of treatment is the ratio of wheat flour, pasta belitung taro, tapioca flour and soybean cake flour is P0 = (100: 0: 0: 0), P1 = (50: 30: 15: 5), P2 = (40: 35: 15: 10), P3 = (35: 40: 10: 15). The results is treatment P3 (35% wheat, 40% belitung taro paste, 10% tapioca flour and 15% soybean cake flour) is the best standard of treatment because it contains 252 Calories of energy lower than 30% of the rice, carbohydrate 37.41% and mostly in the form of oligosaccharides so reducing sugar is low (0.173 mg /dl), the resulting reduction sugar level lower than P0. Wet pasta noodles taro belitung have 3x more fiber than a wet noodle from wheat flour, protein 11.9 g/100 g fulfill of 15% / 100 g (2000 Calories / day), 6.1% fat in the form of saturated fat and fulfill of 10%/100 g (2000 Calories/day), 1.5% ash content and a water content of 41%. Elasticity wet noodle treatment P3 level by 20% and power dropped 0.7 N. The panelists 129emped an the wet noodle pasta belitung taro. Other research to determine how many levels of oligosaccharides wet noodle pasta belitung taro.Keywords: diabetic, wet noodles, belitung taro, tapioca flour, soybean cake flour